Relationship Between Family Support and Exclusive Breastfeeding at Lirung Health Center, Lirung Subdistrict, Talaud Regency - Sutjiato, Margareth (Sean Institute, 2023)
Exclusive breastfeeding is mother's milk that is given to her child immediately after birth until the age of six months without any additional food or drink. During the breastfeeding process, a mother desperately needs support such as family support. Family support is the most important part that has a very big influence on the success of exclusive breastfeeding. This type of research is an analytical survey with a Cross Sectional approach. The population in the study of mothers who had babies aged 6-12 months who were at the Lirung Health Center amounted to 40 respondents. The sample uses total sampling.The purpose of the study was to determine the relationship between family support and exclusive breastfeeding. The results showed that most mother did not receive family support for exclusive breastfeeding, namely 57,5% (23 respondents), and a small proportion of mothers received support from their families for exclusive breastfeeding, which was 42,5% (17 respondents).Chi-Square test results p value is 0.000 smaller than the signifikan value a (0,05). There is a relationship between family support and exclusive breastfeeding at the Lirung Health Center. Suggestions for health agencies to be more active and aggressive in providing counseling and education about exclusive breastfeeding from pregnancy to breastfeeding. Furthermore, for mothers and families to further increase knowledge about the importance of exclusive breastfeeding and more specifically for mothers so that they can continue to provide exclusive breastfeeding so that children get adequate nutritional needs for their growth and development period.